A guide to being the elephant in the room : a study on the residual behaviours stemming from bodyweight stigma - Jayakumar Sandhya Pillai (Nanyang Technological University, 2020)
Body weight and its accompanying stigma in society has always been a personal point of contention for me. From a very young age, I was hyper-aware of the fact that traversing this world in a bigger body would result in lower social capital, hyper visibility and sexual invisibility. In today’s society, albeit the many activistic and effective initiatives in place to combat body-weight biases, the internal mental struggle that comes along with inhabiting a body that society does not seem to accommodate while trying to undo one’s internalised paranoia, is often overlooked. In publicly displaying signs of fatness every day, perceived stereotypes placed upon fat people are reinforced and thus bring about a sense of shame from within. As a result, residual behaviours or ‘by-products of shame’ are performed in an effort to lessen the effect of possessing such mass. My project aims to create a narrative experience for viewers to view the often constricting and debilitating mental processes behind these behaviours. I aim to do so by creating a personal code of conduct titled ‘A Guide To Being The Elephant In The Room’ consisting of three sections each corresponding to a specific ‘by-product of shame’. Brimming with instructional illustrations and texts, this mammoth manual will outline the seemingly absurd sequence of rules that govern my thoughts and actions. The content will work in tandem with deliberate editorial design choices such that the process of flipping through and reading the book in itself will convey the intended ‘by-products’ in each section.